A number of RC pairs consideration of electrical equivalent circuit model of li-ion battery - Kamrueng, Chairat; Kittiratsatcha, Supat; Polmai, Sompob (My University, 2020)
In 20th century, handheld electronic appliances have changed our live style and make things as comfortable as never had before. Of course, the main important part of those devices is the battery. Li-ion battery is the most used not only in those small appliances such as smart phone, tablet, laptop, etc., but also in high power application like in electric vehicle or backup system for power grid. To fully utilize the battery for those applications, a suitable electrical equivalent circuit model must be selected for precise estimation of battery voltage and remaining capacity. Thevenin-based equivalent circuit model with various number of RC pairs has been used in many literatures which give different accuracy of voltages results. This paper proposed the consideration for number of RC pairs for equivalent circuit model using curve fitting method and the goodness of fit results base on the values of root mean square error at several state of charge of battery. The results show good indicator between simple circuit model with low accuracy or complex circuit model with higher accuracy.
Keywords: Battery; Curve Fitting; Equivalent Circuit Model; Exponential; Li-ion model; RC pairs